CLOUD COMPUTING AND SMART TECHNOLOGIES IN AGRICULTURE: A COMPREHENSIVE ANALYSIS OF PRECISION FARMING, RESOURCE MANAGEMENT, AND FUTURE PROSPECTS - Somaning Turwale, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article examines the transformative impact of cloud computing and smart technologies on modern agriculture, focusing on precision farming techniques, resource management solutions, and future technological prospects. The article explores how integrating advanced data collection systems, cloud analytics, and artificial intelligence has revolutionized traditional farming practices. The article analysis encompasses various aspects of smart agriculture, including weather and soil monitoring systems, digital market integration, and supply chain optimization. The article investigates the implementation challenges of these technologies, addressing technical infrastructure requirements, data security concerns, and user adoption strategies. Furthermore, it evaluates the role of emerging technologies in shaping the future of agriculture, examining integration opportunities and sustainability impacts. The article demonstrates how cloud-based solutions have enhanced agricultural efficiency, improved resource utilization, and enabled data-driven decision-making across farming operations. By analyzing current implementations and future trends, this study provides valuable insights into the ongoing digital transformation of agriculture and its potential to address global food security challenges while promoting sustainable farming practices.